Attitude and readiness of utilizing virtual reality simulations in interprofessional education to facilitate prompt and safe hospital discharges in England. - Haider, Sharif; Flynn, Ann; Simpson, J. E. (Social Work Education, 2025)
It can be challenging in England to provide interprofessional education (IPE) in hospitals due to practitioners' availability, high workload, difficulty to backfill, and training costs. Furthermore, most of the IPE training is facilitated by a didactic teaching strategy in a classroom which fails to engage practitioners to understand each other roles and responsibilities, work procedures, policies, issues related to resources, and their pressure points. Technological innovation, in particular virtual reality has opened up a door to overcome these challenges by enabling practitioners to access IPE virtually, and it provides an immersive experience to them. It is not clear whether health and social care practitioners in England would accept and be ready to embrace this type of technology. Hence, this research study aims to understand attitudes and readiness to access virtual reality simulations (VRS) as a teaching modality and pedagogical tool. Health and social care practitioners (n = 22) attended two focus groups after engaging in a VRS and agreed that it could give them valuable learning experiences where they would be able to learn and practice soft skills in a safe environment to discharge people promptly and safely.